Floral development and vasculature in Eriocaulon (Eriocaulaceae) provide insights into the evolution of Poales - De Lima Silva, Arthur [UNESP]; Trovó, Marcelo; Stützel, Thomas; Rudall, Paula J; Sajo, Maria Das Graças [UNESP]; Coan, Alessandra Ike [UNESP] (Oxford University Press (OUP), 2021)
Background and Aims: Floral developmental studies are crucial for understanding the evolution of floral structures and sexual systems in angiosperms. Within the monocot order Poales, both subfamilies of Eriocaulaceae have unisexual flowers bearing unusual nectaries. Few previous studies have investigated floral development in subfamily Eriocauloideae, which includes the large, diverse and widespread genus Eriocaulon. To understand floral variation and the evolution of the androecium, gynoecium and floral nectaries of Eriocaulaceae, we analysed floral development and vasculature in Eriocaulon and compared it with that of subfamily Paepalanthoideae and the related family Xyridaceae in a phylogenetic context. Methods: Thirteen species of Eriocaulon were studied. Developmental analysis was carried out using scanning electron microscopy, and vasculature analysis was carried out using light microscopy. Fresh material was also analysed using scanning electron microscopy with a cryo function. Character evolution was reconstructed over well-resolved phylogenies. Key Results: Perianth reductions can occur due to delayed development that can also result in loss of the vascular bundles of the median sepals. Nectariferous petal glands cease development and remain vestigial in some species. In staminate flowers, the inner stamens can emerge before the outer ones, and carpels are transformed into nectariferous carpellodes. In pistillate flowers, stamens are reduced to staminodes and the gynoecium has dorsal stigmas. Conclusions: Floral morphology is highly diverse in Eriocaulon, as a result of fusion, reduction or loss of perianth parts. The nectariferous carpellodes of staminate flowers originated first in the ancestor of Eriocaulaceae; petal glands and nectariferous branches of pistillate flowers originated independently in Eriocaulaceae through transfer of function. We present a hypothesis of floral evolution for the family, illustrating a shift from bisexuality to unisexuality and the evolution of nectaries in a complex monocot family, which can contribute to future studies on reproductive biology and floral evolution in other groups.
Keywords: Dimery; Eriocaulaceae; Eriocauloideae; Eriocaulon; Floral anatomy; Floral development; Floral evolution; Floral ontogeny; Floral vasculature; Nectary; Poales; Xyrids